A comparison of linear speed, closed-skill agility, and open-skill agility qualities between backcourt and frontcourt adult semiprofessional male basketball players - Scanlan, A. T.; Tucker, P. S.; Dalbo, V. J. (The Journal of Strength and Conditioning Research, 2014)
The measurement of fitness qualities relevant to playing position is necessary to inform basketball coaching and conditioning staff of role-related differences in playing groups. To date, sprinting and agility performance have not been compared between playing positions in adult male basketball players. Therefore, the purpose of this study was to describe and compare linear speed, closed-skill agility, and open-skill agility qualities between backcourt (point guard and shooting guard positions) and frontcourt (small forward, power forward, and center positions) semiprofessional basketball players. Six backcourt (mean ± SD: age, 24.3 ± 7.9 years; stature, 183.4 ± 4.0 cm; body mass, 85.5 ± 12.3 kg; VO2max, 51.9 ± 4.8 ml/kg/min) and 6 frontcourt (mean ± SD: age, 27.5 ± 5.5 years; stature, 194.4 ± 7.1 cm; body mass, 109.4 ± 8.8 kg; VO2max, 47.1 ± 5.0 ml/kg/min) adult male basketball players completed 20-m sprint, closed-skill agility, and open-skill agility performance tests. Magnitude-based inferences revealed that backcourt players (5 m, 1.048 ± 0.027 seconds; 10 m, 1.778 ± 0.048 seconds; 20 m, 3.075 ± 0.121 seconds) possessed likely quicker linear sprint times than frontcourt players (5 m, 1.095 ± 0.085 seconds; 10 m, 1.872 ± 0.127 seconds; 20 m, 3.242 ± 0.221 seconds). Conversely, frontcourt players (1.665 ± 0.096 seconds) held possible superior closed-skill agility performance than backcourt players (1.613 ± 0.111 seconds). In addition, unclear positional differences were apparent for open-skill agility qualities. These findings indicate that linear speed and change of direction speed might be differently developed across playing positions. Furthermore, position-related functions might similarly depend on the aspects of open-skill agility performance across backcourt and frontcourt players. Basketball coaching and conditioning staff should consider the development of position-targeted training drills to improve speed, agility, and cognitive qualities in players.